Analysis of the External and Internal Load in 5vs5 Large Sided Games: Differences Between Different Sized Fields - Giacomo Cofano; Francesca D'Elia; Andrea Piccinno; Italo Sannicandro (OVS LLC, 2021)
The study purpose. The purpose of the study is to analyze and understand the internal and external load in Large Sided Games (LSG) exercises carried out on fields of different sizes, defined as Small - Large Sided Games (SLSG) and Big - Large Sided Games (BLSG), according to the different square meters assigned to each player.  Materials and methods. 22 professional soccer players (average age: 23.59 ± 4.87 years, weight: 77.8 ± 7.6 kg, height: 183.5 ± 7.5 cm, age training: 13.1 ± 1.7). The LSG exercises were carried out on a 60 x 54 m field (270 m2/player), defined as "small" (SLSG) and on a 65 x 60 m field (325 m2/player) defined as "big" (BLSG). During the two LSG exercises, the internal load and the external load were analyzed. LSG exercises were performed with 4 sets of 5 minutes each, with 2 minutes of passive recovery between each set.  Results. The results of the internal load analysis show how the LSG carried out on a SLSG field provides higher and more significant HR values (p < 0.0005) than those emerged during the exercise carried out on a BLSG field. The RPE value is also higher during the SLSG, although statistically no significant difference appears. The analysis of the external load in relation with the observed parameters shows higher values in the BLSG, except for the number of accelerations. Conclusions. In terms of external and internal load, the results of this study showed how the difference of 55 m2/player can radically change the configuration of the two exercises. These differences allow to use both dimensions within a micro-cycle, but in sessions with different goals. The most appropriate sessions for LSGs are the first post-match session in which the rest day is not gone and the fourth session 3 days before the match.